The Effect of Plastic Bottle Biofilter Media with Different Amounts to Reduce the TSS and TDS the Laundry Liquid Waste - Muhammad Razi Ridha; M.Hasbi M.Hasbi; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractLaundry liquid waste is rich in TSS and TDS. Efforts to reduce the level of TSS and  TDS can be conducted by using biofilter. To understand the effect of  plastic bottle biofilter media with different amountsto reduce the TSS and TDS the laundry liquid waste, a research has been done in October-December 2019. There were 3 treatments applied, namely the number of bottles 25 (P1), 50 (P2) and  75 (P3) in anaerobic reactors with 3 replications in each treatments. Each anaerobic reactor contains a series of modiﬁed plastic bottles. The seeding time of the biofilm was 30 days and the retention time of the water was 8 hours. The effectiveness of TSS decrement was 61.7%, 73.8% dan 83.5% in P1, P2, and P3 respectively. While the effectiveness of TDS decrement was 47.1%, 61.3% and 72.1%. in P1, P2, and P3 respectively. Based on this research, it could be concluded that the of  plastic bottle biofilter media with different was able to reduce of TSS dan TDS in the laundry liquid waste. And plastic bottle media with different show a real different decreament of those parameters. Keywords: wastewater, detergent,contaminant, continue system,bacteria.